1977
DOI: 10.1073/pnas.74.1.358
|View full text |Cite
|
Sign up to set email alerts
|

Beta-endorphin: stimulation of growth hormone release in vivo.

Abstract: Two micrograms of f-endorphin (f3-lipotroPin61 il) injected intraventricularly in rats that had been treated with antiserum against somatostatin led to a 6-and 10-fold stimulation of the concentration of plasma growth hormone (somatotropin) measured 10 and 20 min after injection of the peptide, whereas-400 ug of methionine-enkephalin led to a 4-to 6-fold increase of levels of plasma growth hormone at 10 min with a rapid return to basal levels at later time intervals. At doses of 5 and 25 pg, A-endorphin led to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1
1

Year Published

1978
1978
1989
1989

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(24 citation statements)
references
References 17 publications
2
20
1
1
Order By: Relevance
“…The rapid rise in plasma prolactin after iv 1h-ep without any increase in plasma growth hormone is similar to the effect of iv morphine in humans (20); this finding contrasts with the effect of /3h-ep in rats, in which stimulation of both growth hormone and prolactin secretion has been reported (21,22). It has previously been reported that morphine stimulation of growth hormone secretion in the rat is a dose-related phenomenon and does not occur at doses of 50 jug/kg or less (23); similar dose-related effects in rats have been shown with 1h-ep (21,22). Nevertheless, with the icv doses of 3h-ep that we have administered, there was decreased plasma growth hormone secretion in the presence of increased plasma prolactin.…”
Section: Methodscontrasting
confidence: 51%
“…The rapid rise in plasma prolactin after iv 1h-ep without any increase in plasma growth hormone is similar to the effect of iv morphine in humans (20); this finding contrasts with the effect of /3h-ep in rats, in which stimulation of both growth hormone and prolactin secretion has been reported (21,22). It has previously been reported that morphine stimulation of growth hormone secretion in the rat is a dose-related phenomenon and does not occur at doses of 50 jug/kg or less (23); similar dose-related effects in rats have been shown with 1h-ep (21,22). Nevertheless, with the icv doses of 3h-ep that we have administered, there was decreased plasma growth hormone secretion in the presence of increased plasma prolactin.…”
Section: Methodscontrasting
confidence: 51%
“…Although it has been recently shown that opioid peptides elevate the circulating levels of GH and PRL in man and in experimental animals (46)(47)(48)(49)(50), there is a controversy regarding the mechanism ofaction ofopioid peptides to stimulate hormone release. In rat pituitaries, opioid peptides were found to counteract the inhibitory effect of dopamine on PRL secretion in vitro (51).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the synthetic enkephalin analogue, FK-33-824, causes GH release in man (39). None of the opioids appear to act directly at the pituitary level, and it is likely that they influence the release of GH either by modulating the secretion of releasing-inhibiting factors and/or by affecting neurotransmitters (40,41). Evidence supporting the latter hypothesis was provided in a recent study demonstrating that a-adrenergic receptor blockade with phenoxybenzamine or inhibition of NE and EPI synthesis with diethyldithiocarbamate, a dopamine-13-hydroxylase inhibitor, abolished the GH-releasing effect of morphine in the rat (17).…”
Section: Effectsmentioning
confidence: 99%